Holographic imaging with multimode, large free spectral range lasers in photorefractive sillenite crystals - Barbosa, E. A. (Springer, 2005)
The holographic imaging of rigid objects with diode lasers emitting in many wavelengths in a sillenite Bi12TiO20 photorefractive crystal is both theoretically an experimentally investigated. It is shown that, due to the multi-wavelength emission and the typically large free spectral range of this light source, contour fringes appear on the holographic image corresponding to the surface relief, even in single-exposure recordings. The influence of the number of emitted modes on the fringe width is analysed, and the possible applications of the contour fringes in the field of optical metrology are pointed out.